DETERMINANTS OF SAVING PREFERENCES OF VEGETABLE TRADERS IN ISLAMIC FINANCIAL INSTITUTIONS (STUDY ON THE MARKET TRADITIONAL IN KOTANOPAN SUBDISTRICT) - angga angga; muhammad isa; budi gautama (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Financial institutions are institutions whose business activities are related to the financial sector. Islamic financial institutions are one of the instruments used to regulate Islamic economic rules. Islamic financial institutions as part of the sharia economic system in running a business and business cannot be separated from sharia filters. The development of Islamic financial institutions in improving the quality of the economic activities of small and small entrepreneurs by encouraging saving activities and supporting the financing of their economic activities and has made it easier for people to use the services of Islamic financial institutions from various circles of society who have micro businesses, especially in market areas. The use of Islamic financial institutions as an alternative service by traders with ease of transactions without the need to come to Islamic financial institutions to save or withdraw savings. The purpose of this study is to determine whether there is an influence of social factors and service quality on saving preferences in Islamic financial institutions. This research is a quantitative study, using 82 samples of primary data. Data collection techniques are observation, interviews and questionnaires. The data analysis techniques used are validity test, reliability test, normality test, descriptive analysis test, classical assumption test (multicollinearity test and heteroscedasticity test), multiple linear regression analysis test, and hypothesis testing (R2, Ujif and Ujit) with data processing used through the SPSS 22 program. The results of the t-test hypothesis indicate that there is an influence of social factors on saving preferences in Islamic financial institutions as evidenced by that tcount ttable is 1.829 1.664 and there is an influence of service quality on saving preferences in Islamic financial institutions as evidenced by tcount ttable ie 1.696 1.664. Furthermore, this study has a coefficient of determination (R2) obtained R2 of 0.751 or (75.1%). This means that 75.1% of the independent variables affect the dependent variable, while the remaining 24.9% is contributed by other variables outside this research model.